Measurement of South Pole ice transparency with the IceCube LED calibration system - Aartsen, M. G.; Abbasi, R.; Baker, M.; Heereman, D.; Heimann, P.; Heinen, D.; Helbing, K.; Hellauer, R.; Hickford, S.; Hill, G. C.; Hoffman, K. D.; Hoffmann, R.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2013)
The IceCube Neutrino Observatory, approximately 1 km3 in size, is now complete with 86 strings deployed in the Antarctic ice. IceCube detects the Cherenkov radiation emitted by charged particles passing through or created in the ice. To realize the full potential of the detector, the properties of light propagation in the ice in and around the detector must be well understood. This report presents a new method of fitting the model of light propagation in the ice to a data set of in situ light source events collected with IceCube. The resulting set of derived parameters, namely the measured values of scattering and absorption coefficients vs. depth, is presented and a comparison of IceCube data with simulations based on the new model is shown.